Lithium ion battery positive electrode material
By using polymer additives in the positive electrode material of lithium-ion battery, the dispersion of lithium-ion batteries is solved, and the charging status and safety problems of lithium-ion batteries are monitored during overcharge, achieving faster current interruption device turn-on and lower overcharge The temperature improves the battery's overcharge resistance.
Patent Information
- Application Number
- CN202310781058.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
It is difficult for existing lithium-ion batteries to quickly and effectively monitor the charging status when overcharging, resulting in safety problems. The dispersion effect of lithium carbonate in the positive electrode material is poor, affecting the opening speed of the current interruption device.
Add polymer additives, such as NBR, HNBR, SBR, PVP and PAA, to the positive electrode material of lithium ion batteries, to improve the dispersion and stability of lithium carbonate, thereby accelerating the opening of the current interruption device. Enhance the battery's anti-overcharge performance.
By adding polymer additives, the dispersion effect of lithium carbonate in the positive electrode material is significantly improved, the opening time of the current interruption device is shortened, the overcharge resistance of the lithium-ion battery is enhanced, the maximum temperature during overcharge is reduced, and the Battery safety.
Smart Images

Figure CN119230979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode material for lithium ion batteries. Background Art
[0002] Generally, a lithium-ion battery comprises an electrode assembly, a housing for accommodating the electrode assembly, and an electrolyte injected into the housing to allow lithium ions to migrate. The electrode assembly comprises a positive electrode coated with a positive electrode material, a negative electrode coated with a negative electrode material, and a diaphragm disposed between the positive electrode and the negative electrode to prevent short circuits and allow lithium ions to migrate. Among them, the positive electrode material of a lithium-ion battery is a key factor in determining the electrochemical performance, safety performance, energy density, and price cost of the battery. At present, there are many kinds of positive electrode materials for lithium-ion batteries, such as cobalt-based positive electrode materials, nickel-based positive electrode materials, manganese-based positive electrode materials, lithium iron phosphate positive electrode materials, etc.
[0003] Overcharging of lithium-ion batteries will not only cause irreversible damage to the battery, but also may lead to serious safety issues such as combustion and explosion. In response to this, a current interrupt device (CID) is usually installed in the battery. When the battery is overcharged, the pressure inside the battery will increase. When it increases to a certain level, the CID will open to interrupt the current, preventing the battery from further overcharging, thereby avoiding more serious safety issues.
[0004] In order to make CID monitor the charging state of lithium-ion batteries more sensitively and improve the overcharge resistance of lithium-ion batteries, lithium carbonate is usually added to the positive electrode material in the prior art. When the battery is overcharged, lithium carbonate will decompose and produce carbon dioxide gas to increase the pressure inside the battery, thereby achieving the effect of CID opening. The dispersion of lithium carbonate in the positive electrode material has a certain influence on the opening of CID. The better the lithium carbonate is dispersed, the faster the CID will open, which can more effectively avoid safety problems caused by overcharging of lithium-ion batteries. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode material for a lithium ion battery. The positive electrode material for a lithium ion battery comprises a polymer additive as shown in Formula I or Formula II, and by adding the polymer additive as shown in Formula I or Formula II, the lithium carbonate in the positive electrode material is better dispersed, the CID is opened faster, and the lithium ion battery has better anti-overcharge performance.
[0006] According to one aspect of the present invention, there is provided a lithium ion battery positive electrode material, comprising lithium carbonate and a polymer additive as shown in Formula I or Formula II:
[0007]
[0008] In the formula, R 1 , R 2 , R3 , R 4 , R 5 Independently selected from one or more of a hydrogen atom, a halogen atom, a carboxyl group, a hydroxyl group, a cyano group, an isothiocyano group, an ester group, an amide group, an amino group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group and a substituted or unsubstituted aryl group; n is an integer from 1 to 4210, and m is an integer from 1 to 35710.
[0009] In one embodiment, the average molecular weight of the polymer additive is 10,000 to 1,000,000, preferably 100,000 to 500,000, and more preferably 300,000.
[0010] In one embodiment, the polymer additive is selected from one or more of NBR, HNBR, SBR, PVP and PAA, preferably one or more of NBR, HNBR and PVP, and more preferably NBR.
[0011] In one embodiment, the amount of the polymer additive added to the lithium ion battery positive electrode material is 0.001 wt % to 0.1 wt %, preferably 0.01 wt %.
[0012] In one embodiment, 0.3 wt % to 1.0 wt % lithium carbonate is included.
[0013] In one embodiment, 90 wt % to 99 wt % of the positive electrode active material is included.
[0014] In one embodiment, the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt aluminum oxide and lithium iron phosphate.
[0015] In one embodiment, 0.1 wt % to 10 wt % of a binder is further included.
[0016] In one embodiment, the binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose and styrene-butadiene rubber.
[0017] In one embodiment, 0.1 wt % to 10 wt % of a conducting agent is further included.
[0018] In one embodiment, the conductive agent is selected from one or more of conductive carbon black, superconducting carbon black, carbon nanotubes, carbon fibers and graphite conductive agents.
[0019] According to another aspect of the present invention, a lithium ion battery positive electrode plate is provided, comprising the lithium ion battery positive electrode material as described above.
[0020] In one embodiment, the BET surface area of the lithium carbonate particles is 20.2 m2 / g to 23.8m 2 / g, preferably 23.2m 2 / g.
[0021] In one embodiment, the agglomerated size of the lithium carbonate particles is less than 100 μm.
[0022] In one embodiment, the number of agglomerated lithium carbonate particles is no more than 2.
[0023] In one embodiment, the density of the lithium carbonate agglomerates is not greater than 0.08 per square centimeter.
[0024] In one embodiment, there is no agglomeration of lithium carbonate particles in the positive electrode sheet of the lithium ion battery.
[0025] According to another aspect of the present invention, a lithium-ion battery is provided, comprising the lithium-ion battery positive electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Display the overcharge test results of No.1, No.3 and No.5 batteries;
[0027] Figure 2 Display the CCD test results of No.1-No.5 positive electrode pieces;
[0028] Figure 3 Display the overcharge test results of No.6, No.8 and No.10 batteries;
[0029] Figure 4 Display the CCD test results of No.6-No.10 positive electrodes;
[0030] Figure 5 Shows a magnified view of a local area of No. 5 positive electrode plate;
[0031] Figure 6 Shows a magnified view of a local area of the No. 6 positive electrode plate;
[0032] Figure 7 Shows the enlarged image of the local area of No.8 positive electrode plate;
[0033] Figure 8 Display the overcharge test results of No.1, No.11 and No.14 batteries;
[0034] Fig. 9 Displays the CCD test results of the No.11-No.15 positive electrodes. DETAILED DESCRIPTION
[0035] Now, with reference to the accompanying drawings, the specific embodiments of the present invention are described in detail. What is described here is only the preferred embodiment of the present invention, and those skilled in the art can think of other ways to implement the present invention on the basis of the preferred embodiment, and the other ways also fall into the scope of the present invention. In some embodiments, in order to avoid confusion with the present invention, some technical features known in the art are not described.
[0036] definition
[0037] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those of ordinary skill in the art. In the event of a conflict, the present invention (including definitions) shall prevail. Only exemplary methods and materials are described below, and methods and materials similar or equivalent to those described in the present invention can be used for experiments or tests of the present invention. The materials, methods and examples disclosed in the present invention are illustrative only and are not intended to be limiting.
[0038] For the recitation of numerical ranges of the present invention, each intermediate number with the same degree of precision is expressly contemplated. For example, for the range of 6 to 9, the numbers 7 and 8 are contemplated in addition to 6 and 9, and for the range of 6.0 to 7.0, the numbers 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 and 7.0 are expressly contemplated.
[0039] Lithium-ion battery
[0040] An exemplary lithium-ion battery includes a housing and a positive electrode, a negative electrode, a separator and an electrolyte contained in the housing.
[0041] I. Positive electrode
[0042] An exemplary positive electrode may include a positive electrode material and a positive electrode current collector. An exemplary positive electrode material may include a positive electrode active material, a binder, a conductive agent, and lithium carbonate. The positive electrode material is formed on the surface of the positive electrode current collector. The positive electrode material may be formed only on one side of the positive electrode current collector, or may be formed on both the front and back sides of the positive electrode current collector. The positive electrode material may have a thickness of, for example, 10 μm to 200 μm. An exemplary positive electrode current collector is aluminum foil.
[0043] A. Positive electrode active materials
[0044] There is no particular limitation on the positive electrode active material, and exemplary positive electrode active materials are selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate. Preferably, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 .
[0045] Exemplary positive electrode materials may include 90 wt% to 99 wt% of positive electrode active materials. In various cases, exemplary positive electrode materials may include 90 wt% to 99 wt% of positive electrode active materials; 91 wt% to 98 wt% of positive electrode active materials; 92 wt% to 97 wt% of positive electrode active materials; 93 wt% to 96 wt% of positive electrode active materials; or 94 wt% to 95 wt% of positive electrode active materials. In various cases, exemplary positive electrode materials may include no more than 99 wt% of positive electrode active materials; no more than 98 wt% of positive electrode active materials; no more than 97 wt% of positive electrode active materials; no more than 96 wt% of positive electrode active materials; no more than 95 wt% of positive electrode active materials; no more than 94 wt% of positive electrode active materials; no more than 93 wt% of positive electrode active materials; no more than 92 wt% of positive electrode active materials; no more than 91 wt% of positive electrode active materials; or no more than 90 wt% of positive electrode active materials. In various cases, the exemplary positive electrode material may include not less than 90 wt% of the positive electrode active material; not less than 91 wt% of the positive electrode active material; not less than 92 wt% of the positive electrode active material; not less than 93 wt% of the positive electrode active material; not less than 94 wt% of the positive electrode active material; not less than 95 wt% of the positive electrode active material; not less than 96 wt% of the positive electrode active material; not less than 97 wt% of the positive electrode active material; not less than 98 wt% of the positive electrode active material; or not less than 99 wt% of the positive electrode active material. The exemplary positive electrode material may also be substantially composed of the positive electrode active material.
[0046] B. Binder
[0047] Exemplary binders are selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polybenzimidazole, polyimide, polyvinyl acetate, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl methylcellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, polystyrene, polymethyl methacrylate, polyaniline, acrylonitrile-butadiene-styrene copolymer, phenolic resin, epoxy resin, polyethylene terephthalate, polytetrafluoroethylene, polyphenylene sulfide, polyamide-imide, polyetherimide, polyethylene sulfone, polyacetal, polyphenylene oxide, polybutylene terephthalate, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, fluorocarbon rubber and various copolymers. Preferably, one or more of polyvinylidene fluoride, carboxymethyl cellulose and styrene-butadiene rubber are selected. As a preferred, non-limiting example, the binder is polyvinylidene fluoride.
[0048] An exemplary positive electrode material may include 0.1 wt% to 10 wt% of a binder. In various cases, an exemplary positive electrode material may include 0.1 wt% to 10 wt% of a binder; 0.5 wt% to 9.5 wt% of a binder; 1 wt% to 9 wt% of a binder; 3 wt% to 7 wt% of a binder; or 4 wt% to 6 wt% of a binder. In various cases, an exemplary positive electrode material may include no more than 10 wt% of a binder; no more than 9 wt% of a binder; no more than 8 wt% of a binder; no more than 7 wt% of a binder; no more than 6 wt% of a binder; no more than 5 wt% of a binder; no more than 4 wt% of a binder; no more than 3 wt% of a binder; no more than 2 wt% of a binder; no more than 1 wt% of a binder; no more than 0.5 wt% of a binder; or no more than 0.1 wt% of a binder. In various cases, exemplary positive electrode materials may include not less than 0.1 wt % of a binder; not less than 0.5 wt % of a binder; not less than 1 wt % of a binder; not less than 2 wt % of a binder; not less than 3 wt % of a binder; not less than 4 wt % of a binder; not less than 5 wt % of a binder; not less than 6 wt % of a binder; not less than 7 wt % of a binder; not less than 8 wt % of a binder; not less than 9 wt % of a binder; or not less than 10 wt % of a binder.
[0049] C. Conductive agent
[0050] The exemplary conductive agent is selected from one or more of conductive carbon black, superconducting carbon black, carbon nanotubes, carbon fibers and graphite conductive agents. Preferably, the conductive agent is selected from conductive carbon black or superconducting carbon black. More preferably, the conductive agent is superconducting carbon black.
[0051] Exemplary positive electrode materials may include 0.1 wt% to 10 wt% of a conductive agent. In various cases, exemplary positive electrode materials may include 0.1 wt% to 10 wt% of a conductive agent; 0.5 wt% to 9.5 wt% of a conductive agent; 1 wt% to 9 wt% of a conductive agent; 3 wt% to 7 wt% of a conductive agent; or 4 wt% to 6 wt% of a conductive agent. In various cases, exemplary positive electrode materials may include no more than 10 wt% of a conductive agent; no more than 9 wt% of a conductive agent; no more than 8 wt% of a conductive agent; no more than 7 wt% of a conductive agent; no more than 6 wt% of a conductive agent; no more than 5 wt% of a conductive agent; no more than 4 wt% of a conductive agent; no more than 3 wt% of a conductive agent; no more than 2 wt% of a conductive agent; no more than 1 wt% of a conductive agent; no more than 0.5 wt% of a conductive agent; or no more than 0.1 wt% of a conductive agent. In various cases, exemplary positive electrode materials may include not less than 0.1wt% of a conductive agent; not less than 0.5wt% of a conductive agent; not less than 1wt% of a conductive agent; not less than 2wt% of a conductive agent; not less than 3wt% of a conductive agent; not less than 4wt% of a conductive agent; not less than 5wt% of a conductive agent; not less than 6wt% of a conductive agent; not less than 7wt% of a conductive agent; not less than 8wt% of a conductive agent; not less than 9wt% of a conductive agent; or not less than 10wt% of a conductive agent.
[0052] D. Lithium carbonate
[0053] To prevent the battery from being overcharged, an appropriate amount of lithium carbonate is added to the positive electrode material. In order to achieve a better dispersion effect, the lithium carbonate is added in the form of a lithium carbonate suspension, and the amount of the lithium carbonate suspension added is based on the ability to open the CID when the battery is overcharged.
[0054] Exemplary positive electrode materials may include 0.3wt% to 1.0wt% lithium carbonate. In various cases, exemplary positive electrode materials may include 0.3wt% to 1.0wt% lithium carbonate; 0.4wt% to 0.9wt% lithium carbonate; 0.5wt% to 0.8wt% lithium carbonate; or 0.6wt% to 0.7wt% lithium carbonate. In various cases, exemplary positive electrode materials may include no more than 1.0wt% lithium carbonate; no more than 0.9wt% lithium carbonate; no more than 0.8wt% lithium carbonate; no more than 0.7wt% lithium carbonate; no more than 0.6wt% lithium carbonate; no more than 0.5wt% lithium carbonate; no more than 0.4wt% lithium carbonate; or no more than 0.3wt% lithium carbonate. In various cases, exemplary positive electrode materials may include not less than 0.3 wt % lithium carbonate; not less than 0.4 wt % lithium carbonate; not less than 0.5 wt % lithium carbonate; not less than 0.6 wt % lithium carbonate; not less than 0.7 wt % lithium carbonate; not less than 0.8 wt % lithium carbonate; not less than 0.9 wt % lithium carbonate; or not less than 1.0 wt % lithium carbonate.
[0055] E. Preparation method of lithium carbonate suspension
[0056] As a preferred embodiment, the method for preparing the lithium carbonate suspension comprises the following steps:
[0057] Step 1, mixing lithium carbonate powder, grinding medium and dispersing medium, grinding and filtering to obtain a lithium carbonate suspension;
[0058] Step 2: Add a polymer additive to the lithium carbonate suspension, and obtain a stable lithium carbonate suspension after stirring and dispersing.
[0059] The lithium carbonate suspension obtained by the present invention shows better stability after adding the polymer additive, that is, the lithium carbonate is better dispersed in the suspension and maintained for a longer time.
[0060] As a preferred embodiment, the polymer additive is as shown in Formula I or Formula II:
[0061]
[0062]
[0063] In the formula, R 1 , R 2 , R 3 , R 4 , R 5Independently selected from one or more of a hydrogen atom, a halogen atom, a carboxyl group, a hydroxyl group, a cyano group, an isothiocyano group, an ester group, an amide group, an amino group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group and a substituted or unsubstituted aryl group; n is an integer from 1 to 4210, and m is an integer from 1 to 35710.
[0064] As a preferred embodiment, the additive of formula I can be selected from the following polymers:
[0065] Nitrile rubber (NBR)
[0066]
[0067] Hydrogenated Nitrile Rubber (HNBR)
[0068]
[0069] Polymerized styrene butadiene rubber (SBR)
[0070]
[0071] In the formula, n is an integer from 1 to 4210, and m is an integer from 1 to 35710.
[0072] As a preferred embodiment, the additive of formula II can be selected from the following polymers:
[0073] Polyvinylpyrrolidone (PVP)
[0074]
[0075] Polyacrylic acid (PAA)
[0076]
[0077] Wherein, m is an integer from 1 to 35710.
[0078] The exemplary lithium carbonate suspension may include 0.1wt% to 10wt%, preferably 1wt% of the polymer additive shown in Formula I or Formula II. In various cases, the exemplary positive electrode material may include 0.1wt% to 10wt% of the polymer additive shown in Formula I or Formula II; 0.3wt% to 8wt% of the polymer additive shown in Formula I or Formula II; 0.5wt% to 6wt% of the polymer additive shown in Formula I or Formula II; 0.7wt% to 4wt% of the polymer additive shown in Formula I or Formula II; 0.9wt% to 2wt% of the polymer additive shown in Formula I or Formula II; or 1wt% of the polymer additive shown in Formula I or Formula II. In various cases, exemplary positive electrode materials may include no more than 10 wt % of the polymer additive shown in Formula I or Formula II; no more than 8 wt % of the polymer additive shown in Formula I or Formula II; no more than 6 wt % of the polymer additive shown in Formula I or Formula II; no more than 4 wt % of the polymer additive shown in Formula I or Formula II; no more than 2 wt % of the polymer additive shown in Formula I or Formula II; no more than 1 wt % of the polymer additive shown in Formula I or Formula II; no more than 0.5 wt % of the polymer additive shown in Formula I or Formula II; or no more than 0.1 wt % of the polymer additive shown in Formula I or Formula II. In various cases, exemplary positive electrode materials may include not less than 0.1 wt % of the polymer additive shown in Formula I or Formula II; not less than 0.5 wt % of the polymer additive shown in Formula I or Formula II; not less than 1 wt % of the polymer additive shown in Formula I or Formula II; not less than 2 wt % of the polymer additive shown in Formula I or Formula II; not less than 4 wt % of the polymer additive shown in Formula I or Formula II; not less than 6 wt % of the polymer additive shown in Formula I or Formula II; not less than 8 wt % of the polymer additive shown in Formula I or Formula II; or not less than 10 wt % of the polymer additive shown in Formula I or Formula II.
[0079] In order to achieve a better dispersion effect of lithium carbonate in the suspension, as a further preferred embodiment, the average molecular weight of the polymer additive is 10,000 to 1,000,000, preferably 100,000 to 500,000, and more preferably 300,000.
[0080] As a further preferred embodiment, the stable lithium carbonate suspension is dried to obtain lithium carbonate particles, wherein the BET surface area of the lithium carbonate particles is 20.2 m 2 / g to 23.8m 2 / g, preferably 23.2m 2 / g.
[0081] As a further preferred embodiment, step one includes a first process and a second process, wherein the first process includes mixing lithium carbonate powder, grinding medium, and a first dispersion medium and then grinding to obtain a first suspension; the second process includes mixing the first suspension, grinding medium, and a second dispersion medium and then grinding to obtain a lithium carbonate suspension.
[0082] Among them, the exemplary first dispersion medium and the second dispersion medium can be selected from one or more of methanol, ethanol, propanol or N-methyl-2-pyrrolidone respectively; the exemplary grinding medium can be selected from one or more of aluminum oxide particles, zirconium oxide particles or zirconium silicate particles.
[0083] The present invention further provides a stable lithium carbonate suspension. The stable lithium carbonate suspension contains a polymer additive as shown in Formula I or Formula II. The stable lithium carbonate suspension can be prepared by the preparation method as described above.
[0084] The present invention further provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps: adding the stable lithium carbonate suspension of the present invention to a positive electrode slurry containing a positive electrode active material, a binder and a conductive agent.
[0085] The present invention further provides a positive electrode material for a lithium ion battery. The positive electrode material contains a polymer additive as shown in Formula I or Formula II. The positive electrode material can be prepared by the preparation method described above.
[0086] The exemplary positive electrode material may include 0.001wt% to 0.1wt%, preferably 0.01wt% of the polymer additive shown in Formula I or Formula II. In various cases, the exemplary positive electrode material may include 0.001wt% to 0.1wt% of the polymer additive shown in Formula I or Formula II; 0.003wt% to 0.08wt% of the polymer additive shown in Formula I or Formula II; 0.005wt% to 0.06wt% of the polymer additive shown in Formula I or Formula II; 0.007wt% to 0.04wt% of the polymer additive shown in Formula I or Formula II; 0.009wt% to 0.02wt% of the polymer additive shown in Formula I or Formula II; or 0.01wt% of the polymer additive shown in Formula I or Formula II. In various cases, exemplary positive electrode materials may include no more than 0.1wt% of the polymer additive shown in Formula I or Formula II; no more than 0.08wt% of the polymer additive shown in Formula I or Formula II; no more than 0.06wt% of the polymer additive shown in Formula I or Formula II; no more than 0.04wt% of the polymer additive shown in Formula I or Formula II; no more than 0.02wt% of the polymer additive shown in Formula I or Formula II; no more than 0.01wt% of the polymer additive shown in Formula I or Formula II; no more than 0.009wt% of the polymer additive shown in Formula I or Formula II; no more than 0.007wt% of the polymer additive shown in Formula I or Formula II; no more than 0.005wt% of the polymer additive shown in Formula I or Formula II; no more than 0.003wt% of the polymer additive shown in Formula I or Formula II; or no more than 0.001wt% of the polymer additive shown in Formula I or Formula II. In various cases, exemplary positive electrode materials may include not less than 0.001wt% of the polymer additive shown in Formula I or Formula II; not less than 0.003wt% of the polymer additive shown in Formula I or Formula II; not less than 0.005wt% of the polymer additive shown in Formula I or Formula II; not less than 0.007wt% of the polymer additive shown in Formula I or Formula II; not less than 0.009wt% of the polymer additive shown in Formula I or Formula II; not less than 0.01wt% of the polymer additive shown in Formula I or Formula II; not less than 0.02wt% of the polymer additive shown in Formula I or Formula II; not less than 0.04wt% of the polymer additive shown in Formula I or Formula II; not less than 0.06wt% of the polymer additive shown in Formula I or Formula II; not less than 0.08wt% of the polymer additive shown in Formula I or Formula II; or not less than 0.1wt% of the polymer additive shown in Formula I or Formula II.
[0087] An exemplary positive electrode may be prepared by coating a positive electrode slurry including a positive electrode material (which may include a positive electrode active material, a binder, a conductive agent, and lithium carbonate) onto a positive electrode current collector and drying the slurry. The positive electrode material may be further compacted onto the current collector using a pressing method known to a person of ordinary skill in the art. An exemplary positive electrode slurry may be prepared by combining positive electrode material components (positive electrode active material, binder, conductive agent), mixing uniformly by adding a suitable solvent (e.g., N-methylpyrrolidone), and further adding the stable lithium carbonate suspension of the present invention.
[0088] II. Negative electrode
[0089] An exemplary negative electrode may generally include a negative electrode material and a negative electrode current collector. An exemplary negative electrode material may include a negative electrode active material, a binder, and a conductive agent. The negative electrode material is formed on the surface of the negative electrode current collector. The negative electrode material may be formed only on one side of the negative electrode current collector, or on both the positive and negative sides of the negative electrode current collector. The negative electrode material may, for example, have a thickness of 10 μm to 200 μm. There is no particular limitation on the negative electrode active material, and may include carbon, such as natural or artificial graphite. In various cases, the exemplary negative electrode active material may be a carbon composite material, such as a silicon-carbon composite material (Si / C). An exemplary negative electrode current collector is copper foil.
[0090] Exemplary negative electrode materials may include 90 wt% to 99 wt% of negative electrode active materials. In various cases, exemplary negative electrode materials may include 90 wt% to 99 wt% of negative electrode active materials; 91 wt% to 98 wt% of negative electrode active materials; 92 wt% to 97 wt% of negative electrode active materials; 93 wt% to 96 wt% of negative electrode active materials; or 94 wt% to 95 wt% of negative electrode active materials. In various cases, exemplary negative electrode materials may include no more than 99 wt% of negative electrode active materials; no more than 98 wt% of negative electrode active materials; no more than 97 wt% of negative electrode active materials; no more than 96 wt% of negative electrode active materials; no more than 95 wt% of negative electrode active materials; no more than 94 wt% of negative electrode active materials; no more than 93 wt% of negative electrode active materials; no more than 92 wt% of negative electrode active materials; no more than 91 wt% of negative electrode active materials; or no more than 90 wt% of negative electrode active materials. In various cases, exemplary negative electrode materials may include not less than 90 wt% of negative electrode active materials; not less than 91 wt% of negative electrode active materials; not less than 92 wt% of negative electrode active materials; not less than 93 wt% of negative electrode active materials; not less than 94 wt% of negative electrode active materials; not less than 95 wt% of negative electrode active materials; not less than 96 wt% of negative electrode active materials; not less than 97 wt% of negative electrode active materials; not less than 98 wt% of negative electrode active materials; or not less than 99 wt% of negative electrode active materials. Exemplary negative electrode materials may also be substantially composed of negative electrode active materials.
[0091] An exemplary negative electrode may be prepared by coating a negative electrode slurry including a negative electrode material component (which may include a negative electrode active material, a binder, and a conductive agent) onto a negative electrode current collector and drying the slurry. The negative electrode material may be further compacted onto the current collector using a pressing method known to those of ordinary skill in the art. An exemplary negative electrode slurry may be prepared by combining negative electrode material components (negative electrode active material, binder, conductive agent) and adding a suitable solvent (e.g., deionized water).
[0092] In addition, a binder and / or a conductive agent may be optionally included in the negative electrode material and may be the same (or substantially the same) as those described with respect to the positive electrode material, and the present invention will not be repeated.
[0093] III. Diaphragm
[0094] The lithium-ion battery of the present invention has no particular limitation on the separator. An exemplary separator is a separator made of a polymer such as polypropylene (PP) or polyethylene (PE).
[0095] IV. Electrolyte
[0096] The lithium-ion battery of the present invention has no particular restrictions on the electrolyte. For example, it is a non-aqueous electrolyte, and an exemplary non-aqueous electrolyte includes one or more lithium (Li) salts and a non-aqueous solvent. For example, it is an organic electrolyte, and the organic electrolyte is prepared by dissolving a lithium salt in an organic solvent. The lithium salt can be any lithium salt commonly used in the art. An exemplary lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N、LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiCl、LiI、LiN(C x F 2x +1SO 2 )(C y F 2y +1SO 2 ) (wherein x and y are natural numbers) or any mixture thereof. The organic solvent may be any suitable material that can be used as an organic solvent. Exemplary organic solvents are ethylene carbonate, ethyl vinyl ester, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether or a combination thereof.
[0097] In addition to the above-mentioned organic electrolytes, other exemplary electrolytes further include organic solid electrolytes, inorganic solid electrolytes, etc. Examples of the organic solid electrolytes include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfides, polyvinyl alcohol, PVDF, and polymers including ion dissociative groups. Examples of the inorganic solid electrolytes are nitride solid electrolytes, oxynitride solid electrolytes, and sulfide solid electrolytes. Examples of the inorganic solid electrolytes are Li 3 N, LiI, Li 5 NI 2 , Li 3N-LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH and Li 3 PO 4 -Li 2 S-SiS 2 .
[0098] Exemplary lithium-ion batteries can be prepared using methods known to those of ordinary skill in the art. Specific embodiments
[0100] The following examples describe several embodiments of the present invention and are provided to illustrate the invention but are not intended to limit the invention thereto.
[0101] Example 1: Preparation of a stable lithium carbonate suspension
[0102] Step 1, using two-stage sand milling to prepare a lithium carbonate suspension: the first stage (first process) includes mixing lithium carbonate powder, grinding medium, and a first dispersing medium in a first sand mill and then grinding to obtain a first suspension; the second stage (second process) includes mixing the first suspension, grinding medium, and a second dispersing medium in a second sand mill and then grinding to obtain a lithium carbonate suspension;
[0103] Step 2: Add a polymer additive as shown in Formula I or Formula II to the lithium carbonate suspension, and stir and disperse to obtain a stable lithium carbonate suspension.
[0104] Example 2: BET surface area test of lithium carbonate particles
[0105] The stable lithium carbonate suspension prepared in Example 1 is dried to obtain lithium carbonate particles, and the BET surface area of the lithium carbonate particles is further determined by a nitrogen low-temperature adsorption method: the sample is degassed by heating and vacuuming to remove impurity gases adsorbed on the surface; the sample is weighed and placed in liquid nitrogen, and the nitrogen adsorption amount of the sample is determined at different preset pressure points at the liquid nitrogen temperature to obtain an adsorption isotherm; the data is processed by a computer, and the BET surface area is calculated based on the adsorption isotherm.
[0106] The following is an investigation of the effects of the amount of additive added, the type of additive, and the average molecular weight of the additive on the BET surface area of lithium carbonate particles.
[0107] (1) Effect of additive amount on BET surface area of lithium carbonate particles
[0108] By adjusting the amount of additive added (the additive is NBR, and the average molecular weight is 300000), the BET surface area of lithium carbonate particles was tested, and the results are shown in Table 1.
[0109] Table 1 Effect of additive amount on BET surface area of lithium carbonate particles
[0110] Addition amount (wt%) <![CDATA[BET surface area (m 2 / g)]]> 0 24.1 0.001 24.3 0.01 23.6 0.1 23.8 1 23.2 10 21.4 20 20.8 30 13.9
[0111] (2) Effect of the average molecular weight of additives on the BET surface area of lithium carbonate particles
[0112] By adjusting the average molecular weight of the additive (the additive is NBR, and the addition amount is 1 wt %), the BET surface area of the lithium carbonate particles was tested. The results are shown in Table 2.
[0113] Table 2 Effect of the average molecular weight of additives on the BET surface area of lithium carbonate particles
[0114]
[0115]
[0116] (3) Effect of additive types on the BET surface area of lithium carbonate particles
[0117] By adjusting the type of additive (addition amount is 1%), the BET surface area of lithium carbonate particles was tested. The results are shown in Table 3.
[0118] Table 3 Effect of additive types on BET surface area of lithium carbonate particles
[0119] additive Average molecular weight <![CDATA[BET surface area (m 2 / g)]]> NBR 300000 23.2 HNBR 180000 23.8 SBR 500000 21.7 PVP 360000 20.2 PAA 450000 20.7
[0120] Example 3: Battery overcharge test and CCD test
[0121] Lithium-ion battery for overcharge test: positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The negative electrode active material is a silicon-carbon composite material, and the electrolyte is an organic electrolyte.
[0122] The stable lithium carbonate suspension prepared in Example 1 was added to the slurry of the positive electrode material to examine the effects of the amount of additive, the type of additive and the average molecular weight of the additive on battery overcharge. Battery overcharge test conditions: 8A-6V (100% SOC).
[0123] (1) Effect of additive dosage on battery overcharge
[0124] By adjusting the amount of additives (the additive is NBR, the average molecular weight is 300000), the battery is overcharged and the results are shown in Table 4 and Figure 1 As shown (No. 1 has no additive added, as a comparative example). Among them, the batteries with additive amounts of 0.1wt%, 1wt% and 10wt% have shorter CID opening time and much lower maximum temperature of the battery than the batteries with no additive added and 30wt% additive added; the battery with 1wt% additive has the shortest CID opening time and the lowest maximum temperature of the battery.
[0125] Table 4 Effect of additive amount on battery overcharge
[0126] No. Addition amount (wt%) <![CDATA[BET surface area (m 2 / g)]]> CID opening time (s) Maximum temperature(℃) 1 0 24.1 2202 131 2 0.1 23.8 2182 104 3 1 23.2 2174 87 4 10 21.4 2179 98 5 30 13.9 2214 155
[0127] Furthermore, a charge coupled device (CCD) was used to test the dispersion effect of lithium carbonate in the positive electrode sheet. Figure 2 As shown, it can be seen that the lithium carbonate dispersion effect is better in the pole pieces with addition amounts of 0.1wt%, 1wt% and 10wt%.
[0128] (2) Effect of average molecular weight of additives on battery overcharge
[0129] By adjusting the average molecular weight of the additive (the additive is NBR, the addition amount is 1wt%), the battery is overcharged and the results are shown in Table 5 and Figure 3 As shown. Among them, compared with the batteries with average molecular weights of 100000 and 1000000, the batteries with average molecular weights of 100000, 300000 and 500000 have shorter CID opening time and much lower maximum temperature of the batteries; the battery with average molecular weight of 300000 has the shortest CID opening time and the lowest maximum temperature of the batteries; the above performance of the battery with average molecular weight of 100000 is close to that of the battery with average molecular weight of 300000.
[0130] Table 5 Effect of average molecular weight of additives on battery overcharge
[0131] No. Average molecular weight <![CDATA[BET surface area (m 2 / g)]]> CID opening time (s) Maximum temperature(℃) 6 10000 20.8 2204 136 7 100000 23.8 2177 92 8 300000 23.2 2174 87 9 500000 21.2 2186 113 10 1000000 14.2 2256 156
[0132] Furthermore, the dispersion effect of lithium carbonate in the positive electrode sheet was tested using CCD, such as Figure 4 As shown, it can be seen that the lithium carbonate dispersion effect is better in the electrodes with average molecular weights of 100,000, 300,000 and 500,000.
[0133] Figure 5-Figure 7 The enlarged images of the local areas of the pole pieces of Examples No. 5, 6, and 8 are shown in sequence. 2The number of white spots in the electrode area is >2pcs (2), 1-2pcs, and 0pcs, and the size of the white spots is ≥100μm, 0-100μm, and 0μm (diameter). The white spots are agglomerates of lithium carbonate. Figure 5 It can be clearly seen that there is lithium carbonate agglomeration in the middle part of the right picture, and it is even possible that the agglomeration has wrapped the positive electrode material. Figure 6 It can be seen that there is a cluster in the right picture. Figure 7 It can be seen that there is no agglomeration in the right figure. The white dots are positive electrode materials, and their diameter is generally less than 20um. Therefore, the electrodes No. 5, 6, and 8 are bad electrodes, acceptable electrodes, and preferred electrodes, respectively. In other words, the density of lithium carbonate agglomeration in acceptable electrodes is no more than 2pcs / 25cm 2 =0.08 pieces / cm2, and the size of each agglomerate of lithium carbonate particles is less than 100 μm.
[0134] (3) Effect of additive types on battery overcharge
[0135] By adjusting the type of additives (addition amount is 1wt%), the battery is overcharged and the results are shown in Table 6 and Figure 8 As shown. Among them, the CID opening time of the battery with additives is shorter than that of the battery without additives, and the maximum temperature of the battery is much lower; the batteries with NBR, HNBR and PVP have better performance than those with SBR and PAA; and the battery with NBR has the best performance.
[0136] Table 6 Effect of additive types on battery overcharge
[0137]
[0138]
[0139] Furthermore, the dispersion effect of lithium carbonate in the positive electrode sheet was tested using CCD, such as Fig. 9 As shown, it can be seen that the dispersion effect of lithium carbonate in the electrodes with five additives is good.
[0140] It can be seen from the above examples that when the BET surface area is 20.2 m 2 / g to 23.8m 2 / g, the CID opening time is shorter and the maximum temperature of the battery is lower. When the additive is NBR, the average molecular weight is 300000, and the addition amount is 1wt%, the maximum overcharge temperature can be effectively reduced from 131℃ to 87℃.
[0141] The above description of various embodiments of the present invention is provided to one of ordinary skill in the relevant art for the purpose of description. It is not intended that the present invention be exclusive or limited to a single disclosed embodiment. As above, a person of ordinary skill in the field of the above teachings will understand the various substitutions and variations of the present invention. Therefore, although some alternative embodiments are specifically described, a person of ordinary skill in the art will understand or relatively easily develop other embodiments. The present invention is intended to include all substitutions, modifications and variations of the present invention described herein, as well as other embodiments that fall within the spirit and scope of the present invention described above.
Claims
1. A positive electrode material for a lithium ion battery, characterized in that: It includes lithium carbonate and a polymer additive as shown in Formula I or Formula II: In the formula, R1, R2, R3, R4, and R5 are independently selected from one or more of a hydrogen atom, a halogen atom, a carboxyl group, a hydroxyl group, a cyano group, an isothiocyano group, an ester group, an amide group, an amino group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, and a substituted or unsubstituted aryl group; n is an integer from 1 to 4210, and m is an integer from 1 to 35710.
2. The lithium-ion battery positive electrode material according to claim 1, characterized in that The average molecular weight of the polymer additive is 10,000 to 1,000,000, preferably 100,000 to 500,000, and more preferably 300,000.
3. The positive electrode material for lithium-ion batteries according to claim 1, characterized in that: The polymer additive is selected from one or more of NBR, HNBR, SBR, PVP and PAA, preferably one or more of NBR, HNBR and PVP, more preferably NBR.
4. The lithium-ion battery positive electrode material according to claim 1, characterized in that The amount of the polymer additive added to the lithium ion battery positive electrode material is 0.001wt% to 0.1wt%, preferably 0.01wt%.
5. The lithium-ion battery positive electrode material according to claim 1, characterized in that: 0.3wt% to 1.0wt% of lithium carbonate is included.
6. The lithium-ion battery positive electrode material according to claim 1, characterized in that: The positive electrode active material is included in an amount of 90 wt % to 99 wt %.
7. The positive electrode material for lithium-ion batteries according to claim 6, characterized in that: The positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt aluminum oxide and lithium iron phosphate.
8. The lithium-ion battery positive electrode material according to claim 1, characterized in that: The composition further comprises 0.1 wt % to 10 wt % of a binder.
9. The lithium-ion battery positive electrode material according to claim 8, characterized in that The binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose and styrene-butadiene rubber.
10. The lithium-ion battery positive electrode material according to claim 1, characterized in that: 0.1 wt % to 10 wt % of a conducting agent is also included.
11. The lithium-ion battery positive electrode material according to claim 10, characterized in that: The conductive agent is selected from one or more of conductive carbon black, superconducting carbon black, carbon nanotubes, carbon fibers and graphite conductive agents.
12. A positive electrode plate for a lithium ion battery, characterized in that: The invention comprises the positive electrode material for a lithium ion battery according to any one of claims 1 to 11.
13. The positive electrode plate of a lithium-ion battery according to claim 12, characterized in that: The BET surface area of the lithium carbonate particles is 20.2 m 2 / g to 23.8m 2 / g, preferably 23.2m 2 / g.
14. The positive electrode plate of a lithium-ion battery according to claim 12, characterized in that: The agglomerated size of the lithium carbonate particles is less than 100 μm.
15. The positive electrode plate of a lithium-ion battery according to claim 14, characterized in that: The number of agglomerated lithium carbonate particles is no more than 2.
16. The positive electrode plate of a lithium-ion battery according to claim 14, characterized in that: The density of the lithium carbonate agglomerates is no more than 0.08 per square centimeter.
17. The positive electrode plate of a lithium-ion battery according to claim 12, characterized in that: There is no agglomeration of lithium carbonate particles in the positive electrode plate of the lithium ion battery.
18. A lithium ion battery, comprising the lithium ion battery positive electrode sheet according to claim 12.
Citation Information
Cited By
Battery cell, battery device, electric device, and energy storage device
WO2026200074A1
